계획적 행동이론을 이용한 여대생의 유제품 섭취 행동 분석 - 김경원; 신은미 (Korean journal of community nutrition, 2003)
This study was designed to explain the intentions and consumption of dairy foods among university female students. The factors related to intentions of consumption or actual consumption of dairy foods were identified within the theory of planned behavior. The survey questionnaire, developed using open-ended questions (n=35) , was administered to university female students (n:184) Subjects completed information regarding attitudes, subjective norms, perceived control, intentions and consumption of dairy foods. Correlation analysis and multiple regression were used to study the association of factors with intentions and consumption of dairy foods. Subjects showed relatively low intention to consume dairy foods (-0.4 $±$ 1.6 from a scale of -4-14). They ate 1.2 $±$ 0.9 servings of dairy foods a day and 52.2% of subjects had less than a serving a day, showing inadequate consumption of dairy foods. All three factors, attitudes, subjective norms and perceived control were significantly correlated to the intentions to take dairy foods regularly (r : 0.26-0.27) . Multiple regression results, however, revealed that subjective norms (p < 0.01) and perceived control (p < 0.05) contributed to the model of explaining intentions, while attitudes did not (model $R^2$ : 0.154) . To predict and explain actual consumption of dairy foods, two regression models were examined. In the first model, perceived control was significant in predicting dairy foods consumption, while attitudes and subjective norms were not. In the second model, intentions and perceived control were significantly related to actual consumption of dairy foods, providing the empirical evidence of the theory (model $R^2$: 0.121) These results suggest that perceived control was significant in explaining actual behavior as well as intentions. This study suggests that nutrition education to increase dairy foods consumption for young adults should focus on increasing perception of control and eliciting social support from respected others.